Foreign Private Investment in Developing Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
Since the early 1970s foreign direct and portfolio equity investment flows into developing countries, although continuing to increase in absolute terms, have been relatively less important than in previous years, as foreign private capital flows have been dominated by debt-creating bank credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet